Pengaruh Penggunaan Teknologi Informasi Terhadap Kepuasan Kerja Karyawan (Studi Kasus pada PT. Pos Indonesia (Persero) Surakarta) - Mellinda, Ayu; , Ahmad Mardalis, SE.,MBA (2017)
The purpose of this study are: 1) To determine the level of satisfaction of employees at PT. Pos Indonesia (Persero) Surakarta; 2) To determine the use of information technology PT. Pos Indonesia (Persero) Surakarta; 3) To determine the effect of the use of information technology to job satisfaction of employees at PT. Pos Indonesia (Persero) Surakarta. This study used quantitative descriptive data. The sample in this study were 69 respondents. The sampling technique using a simple random sampling or random sampling. The analytical method used is to test the validity, reliability test, the first performed the classic assumption test including normality test, multicolinearity test, and test heterokedastisitas. By hypothesis testing using multiple linear regression analysis, the significance test together (Test-F) and partial significance test (t-test) and the coefficient of determination (R2). Results: 1) The level of job satisfaction of employees at PT. Pos Indonesia (Persero) Surakarta quite good because their leaders who can provide encouragement and the close attention the work performed by the employee. 2) The use of information technology at PT. Pos Indonesia (Persero) Surakarta quite good because of the use of information technology to improve the effectiveness of employees. 3) The use of information technology and significant positive effect on job satisfaction of employees at PT. Pos Indonesia (Persero) Surakarta.